2010
DOI: 10.2176/nmc.50.595
|View full text |Cite
|
Sign up to set email alerts
|

Primary Diffuse Large B-Cell Lymphomas of the Temporoparietal Dura Mater and Scalp Without Intervening Skull Bone Invasion -Case Report-

Abstract: A 72-year-old man presented with an extremely rare case of primary diffuse large B-cell lymphomas (DLBCLs) of the dura and scalp existing independently without intervening cranial vault invasion. The patient presented with an indolent mass lesion at the left temporal parietal scalp. Magnetic resonance imaging and computed tomography revealed a solid homogeneously enhanced mass in the left temporoparietal scalp, and an extra-axial intracranial mass that existed just below the scalp without intervening skull inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…We did not perform a simple needle biopsy for scalp tumor, instead craniectomy with both scalp bone and intracranial tumor excisions was carried out. As proposed by Ochiai et al (5), it seems that needle biopsy of the scalp tumor, which does not cause significant neurologic symptoms, may obviate surgery, leading the treatment plan to appropriate radiotherapy and chemotherapy. Treatment of diffuse large cell lymphomas (DL-CLs) is primarily with cytotoxic agents, with or without radiation therapy.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We did not perform a simple needle biopsy for scalp tumor, instead craniectomy with both scalp bone and intracranial tumor excisions was carried out. As proposed by Ochiai et al (5), it seems that needle biopsy of the scalp tumor, which does not cause significant neurologic symptoms, may obviate surgery, leading the treatment plan to appropriate radiotherapy and chemotherapy. Treatment of diffuse large cell lymphomas (DL-CLs) is primarily with cytotoxic agents, with or without radiation therapy.…”
Section: Discussionmentioning
confidence: 97%
“…In our case, although microscopic examination revealed lymphoid infiltration, there was only minimal imaging signs of bone involvement. It has been suggested that presence of the tumor on the scalp and dura sides, without skull bone invasion between might be one of the characteristics of lymphoma (5). We did not perform a simple needle biopsy for scalp tumor, instead craniectomy with both scalp bone and intracranial tumor excisions was carried out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malignant lymphoma should be considered in the differential diagnosis of scalp and dural tumors without intervening skull bone invasion. 7 In contrast to primary skull lymphomas, Primary Breast Lymphoma is a rare entity and accounts for only 0.15% of all the malignant breast lesions. 8 In breasts, the B-cell lymphoma is reported to be more prevalent than the T-cell lymphomas.…”
Section: Discussionmentioning
confidence: 99%
“…A literature search found 93 cases of dural based lymphomas (Table 1). Of these, 67 (72%) were described as MALT or marginal zone lymphoma, 6,9,10,12,15,16,20–25,2835,41,44,6270 9 were diffuse large B-cell lymphoma, 11,14,18,27,36,37,42,71 and 6 were follicular lymphoma. 3,17,26,38,40,72 Six were described as small lymphocytic lymphoma 13,14,73,74 or B-cell lymphoproliferative disorder of CLL type, 75 but the four of these that were described prior to the establishment of the REAL-WHO criteria may have actually been MALT/Marginal zone lymphoma since immunophenotypical analysis was not performed.…”
Section: Discussionmentioning
confidence: 99%